2014
DOI: 10.1002/eji.201343935
|View full text |Cite
|
Sign up to set email alerts
|

Wiskott–Aldrich syndrome protein deficiency in natural killer and dendritic cells affects antitumor immunity

Abstract: Wiskott-Aldrich syndrome (WAS) is a primary immunodeficiency caused by reduced or absent expression of the WAS protein (WASP). WAS patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 22 publications
(31 reference statements)
1
28
0
1
Order By: Relevance
“…It has previously been shown that WASp − mice bred to tumor susceptible Cdkn2a knockout background also show earlier death and poor rejection of injected B16 melanoma cells when compared to WASp + mice. 30 Poor tumor survival and rejection capacity is at least partly caused by reduced tumor surveillance by WASp − NK cells and cytotoxic T cells as we and others have shown. 30-34 It is therefore likely that poor tumor prognosis in p53 +/- WASp − could be explained by aberrant tumor surveillance by WASp − cytotoxic cells.…”
Section: Discussionmentioning
confidence: 81%
“…It has previously been shown that WASp − mice bred to tumor susceptible Cdkn2a knockout background also show earlier death and poor rejection of injected B16 melanoma cells when compared to WASp + mice. 30 Poor tumor survival and rejection capacity is at least partly caused by reduced tumor surveillance by WASp − NK cells and cytotoxic T cells as we and others have shown. 30-34 It is therefore likely that poor tumor prognosis in p53 +/- WASp − could be explained by aberrant tumor surveillance by WASp − cytotoxic cells.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, DCs from WAS patients show defects in phagocytosis [29,30] and in their ability to form podosomes and lamellipodia, resulting in defective migratory responses [31,32] and therefore also contribute to the effect. Although in the study by Catucci et al, the numbers of splenic DCs were comparable in LPS-treated Was −/− and WT mice [11], the impaired DC migration toward SLOs and the incomplete redistribution to T-cell areas that has previously been observed in studies involving Was −/− DCs [31] might also contribute to the defect in tumor immunosurveillance.…”
mentioning
confidence: 76%
“…This link between WAS and increased cancer incidence has been explored by Catucci et al [11] in the present issue of the European Journal of Immunology. In order to test the hypothesis that Was deficiency affects tumor immunosurveillance in vivo, the authors crossed Was −/− mice to Cdkn2a −/− mice.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Cellular factors that foster NK-DC crosstalk has emerged to be critical in the regulation of antitumor responses. Gene silencing or gene deficiency of WAS protein in DC impaired NK-DC conjugate formation, impaired NK activation, enhanced tumor growth and enhanced metastasis of melanoma cells [36,37]. Enhanced tumor incidence and onsets of B16 melanoma and methylcholanthrene-induced fibrosarcoma were observed in the conditional knockout mice in which IL-27 was specifically deleted in DC [38].…”
Section: Enhancing Nk-dc Crosstalk In Cancer Immunotherapymentioning
confidence: 99%